Forecasting a winner for Malaysian Cup 2013 using soccer simulation model - Mat Yusof, Muhammad; Omar Fauzee, Mohd Sofian; Abdul Latif, Rozita (2014)
This paper investigates through soccer simulation the calculation of the probability for each team winning Malaysia Cup 2013.Our methodology used here is we predict the outcomes of individual matches and then we simulate the Malaysia Cup 2013 tournament 5000 times.As match outcomes are always a matter of uncertainty, statistical model, in particular a double Poisson model is used to predict the number of goals scored and conceded for each team.Maximum likelihood estimation is use to measure the attacking strength and defensive weakness for each team. Based on our simulation result, LionXII has a higher probability in becoming the winner, followed by Selangor, ATM, JDT and Kelantan.Meanwhile, T-Team, Negeri Sembilan and Felda United have lower probabilities to win Malaysia Cup 2013. In summary, we find that the probability for each team becominga winner is small, indicating that the level of competitive balance in Malaysia Cup 2013 is quite high